A meta-analysis of pharmacotherapy for social anxiety disorder: an examination of efficacy, moderators, and mediators. (11th February 2017) - Curtiss, Joshua; Andrews, Leigh; Davis, Michelle; Smits, Jasper; Hofmann, Stefan G.
ABSTRACT: Introduction : Social anxiety disorder (SAD) is among the most prevalent mental disorders, associated with impaired functioning and poor quality of life. Pharmacotherapy is the most widely utilized treatment option. The current study provides an updated meta-analytic review of the efficacy of pharmacotherapy and examines moderators and mediators of treatment efficacy. Areas Covered : A comprehensive search of the current literature yielded 52 randomized, pill placebo-controlled trials of pharmacotherapy for adults diagnosed with SAD. Data on potential mediators of treatment outcome were collected, as well as data necessary to calculate pooled correlation matrices to compute indirect effects. Expert Opinion : The overall effect size of pharmacotherapy for SAD is small to medium (Hedges' g =  0.41). Effect sizes were not moderated by age, sex, length of treatment, initial severity, risk of study bias, or publication year. Furthermore, reductions in symptoms mediated pharmacotherapy's effect on quality of life. Support was found for reverse mediation. Future directions may include sustained efforts to examine treatment mechanisms of pharmacotherapy using rigorous longitudinal methodology to better establish temporal precedence.